2018
DOI: 10.1111/kykl.12196
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Drugs, Alcohol and Subjective Well‐Being: Selection or Causation?

Abstract: Summary This paper estimates the effects of risky behaviors (e.g., smoking, alcohol, marijuana, risky sex) on subjective well‐being. To identify these effects from endogenous sorting, I use information from the 1997 National Longitudinal Survey of Youth and a system of simultaneous equations for participation in four risky activities and formation of individual happiness. My results provide evidence that smoking and alcohol decrease subjective well‐being by 2.5% and 2.4%, respectively. By contrast, the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…In a prior study (31), excessive alcohol can increase an individual's psychological distress, and thereby reduce the subjective well-being related to the individual's inherent positive emotions. Other studies (6,7,19) have shown that dangerous behaviors such as alcohol abuse significantly reduce subjective well-being. In this program, education such as understanding alcohol addiction and finding positive ways to relieve stress by role-playing may help the participants to recognize inherent positive emotions and to self-regulate negative emotions such as anger.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a prior study (31), excessive alcohol can increase an individual's psychological distress, and thereby reduce the subjective well-being related to the individual's inherent positive emotions. Other studies (6,7,19) have shown that dangerous behaviors such as alcohol abuse significantly reduce subjective well-being. In this program, education such as understanding alcohol addiction and finding positive ways to relieve stress by role-playing may help the participants to recognize inherent positive emotions and to self-regulate negative emotions such as anger.…”
Section: Discussionmentioning
confidence: 96%
“…Subjective well-being is a self-assessment of an individual's overall life (5), and is strongly related to abuse of substances such as alcohol (6)(7)(8). An alcoholrelated inmate is a problematic drinker who failed to abstain from drinking alcohol, whose self-esteem is low due to negative emotions such as depression, anger, and anxiety, and who may blame others and the environment rather than himself, for his problem (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other covariates: Based on literature and other hypothesised predictors of subjective well-being and /or chronic diseases, the following covariates were controlled for: level of education [26]; current employment status [18]; income levels [17]; marital status [27]; age [28]; fruit and vegetable consumption [29]; rural/urban resident location [30]; alcohol consumption and tobacco consumption [31].…”
Section: Methodsmentioning
confidence: 99%
“…15 We stress that the estimates that we report do not imply causation. Our variables may capture the effect of other variables omitted from the specification, noticeably those related to the benefits and costs of deception, including, e.g., family or peer effects (for related discussions, see Gwozdz et al, 2019;Bucciol et al, 2013;Nikolaou, 2019).…”
Section: Regression Analysesmentioning
confidence: 99%